Productivity and quality of sweet potato roots propagated by mini-cuttings with different trays and seedling ages - Cardoso,Antonio Ismael Inácio (2021)
ABSTRACT The use of mini-cuttings is an option for obtaining sweet potato propagules of excellent quality. The objective of this research was to evaluate the production and quality of sweet potato roots propagated by mini-cuttings in different types of trays and ages of seedlings. Six treatments, resulting from the factorial 2x3, were evaluated: two types of trays (162 and 200 cells, with 31 and 18 mL of substrate per cell, respectively) and three ages of seedlings (39, 46 and 53 days after placement of mini-cuttings in trays), in a randomized block design, with five replications. Seedlings characteristics, production and quality of roots were evaluated. Higher number and dry weight of leaves per seedling were observed in the tray with 162 cells than in trays with 200 cells. The younger seedlings (39 days) had a lower number of leaves, dry weight of leaves, stem, roots ant total (leaves + stem + roots) than seedlings of other ages. There was no difference in root production depending on the type of tray, regardless of the age of the seedlings. For the 162-cell tray, the age of the seedlings did not affect the production of roots. On the other hand, for the 200-cell tray, higher roots production was observed on seedlings 39 days age compared to seedlings with 53 days. No differences were observed among the roots of different treatments for titratable acidity, and levels of sucrose, reducing sugars ant total sugars. It is recommended to avoid old seedlings, that is, it is recommended to use seedlings with a maximum of 43 days after planting of mini-cuttings for trays with 200 cells, while for trays with 162 cells no difference in root production was observed with the different ages of the seedlings.